Manajemen Mutu Perguruan Tinggi (Sebuah Konsep tentang Mutu Perguruan Tinggi Swasta) - Endah Christianingsih (PUBLICA, 2011)
People considers the quality of private university graduate is not as good as the quality of state university. It might be true especially at the time where private university hasnt followed the process of selection system for the students candidate. Along with the time, the improvement of qualified students that will be accepted, the improvement of qualified lecturer, and the accreditation issue have selected the private university that has not fulfilled the required conditions and even better than state university (Directorate General of Higher Education, National Education Department). If it seen from the University Web Ranking, Universities in Indonesia by 2011, the private university has taken the sixth, eighth, eleventh, and twentieth rank, and the rest of them are dominated by the state university.What have been described above surely become the challenge for the private university. Therefore, the private university should more concern to the quality. The quality of higher education is comprehended as the combination of its product characteristics and customer need, especially students (primer customer) and work place (tarsier customer) (Tampubolon, 2001:74). For the reason of sustainability, it will be better if the private university takes this issue with the hard effort and willing to change and does the continuously improvement to reach the quality standard wanted by the stakeholders.